2019
DOI: 10.1111/jcmm.14275
|View full text |Cite
|
Sign up to set email alerts
|

PI3‐kinase/Akt pathway‐regulated membrane transportation of acid‐sensing ion channel 1a/Calcium ion influx/endoplasmic reticulum stress activation on PDGF‐induced HSC Activation

Abstract: Acid‐sensing ion channel 1a (ASIC1a) allows Na + and Ca 2+ flow into cells. It is expressed during inflammation, in tumour and ischaemic tissue, in the central nervous system and non‐neuronal injury environments. Endoplasmic reticulum stress (ERS) is caused by the accumulation of misfolded proteins that interferes with intracellular calcium homoeostasis. Our recent reports showed ASIC1a and ERS are involved in liver fibrosis progression, particularly in hepatic ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Our previous studies have confirmed that PcTx1 reversed the enhancing effect of extracellular acidification on ASIC1a protein and mRNA expression in articular chondrocytes (Gao et al, 2019;Wu et al, 2019). Similarly, the increased expression and membrane trafficking of ASIC1a induced by PDGF stimulation were inhibited by PcTx1 (Zuo et al, 2019).…”
Section: Drugssupporting
confidence: 64%
See 2 more Smart Citations
“…Our previous studies have confirmed that PcTx1 reversed the enhancing effect of extracellular acidification on ASIC1a protein and mRNA expression in articular chondrocytes (Gao et al, 2019;Wu et al, 2019). Similarly, the increased expression and membrane trafficking of ASIC1a induced by PDGF stimulation were inhibited by PcTx1 (Zuo et al, 2019).…”
Section: Drugssupporting
confidence: 64%
“…A similar signaling pathway is also involved in the process of platelet-derived growth factor (PDGF), regulating the expression and membrane trafficking of ASIC1a (Zuo et al, 2019). The expression and membrane trafficking of ASIC1a protein were remarkably increased in PDGF-stimulated hepatic stellate cells.…”
Section: Neurotrophinsmentioning
confidence: 99%
See 1 more Smart Citation
“…How ASIC1a regulates m 6 A modification through METTL3 in liver fibrosis remains to be explored. Activation of ASIC1a channels induces extracellular Ca 2+ influx 13 . Another study found that the protein SUMO level is affected by changes in intracellular calcium levels 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown the critical role of the mitogen PDGF as well as its receptor PDGF receptor-b (PDGFRb) in HSC proliferation and migration (Wong et al, 1994;Kostallari et al, 2018). The extent of inflammation so as fibrosis is correlated with the expression of PDGF in patients with chronic liver diseases (Zuo et al, 2019). Interestingly, the mRNA expression of PDGFRb was confirmed in both quiescent and activated HSCs, but protein production was mainly limited to the activated cells (Henderson et al, 2013).…”
Section: Platelet-derived Growth Factormentioning
confidence: 99%